Assessment of Sanitation Inspection Results of Refilled Drinking Water Depots in the Working Area of Tambak Wedi Public Health Center, Surabaya City, in 2020–2022 - Muslim, Muhammad Hanif; Rahadian Wicaksono1, Rizky; Subhi, Misbahul; Joegiantoro, Rudy; Rupiwardani , Irfany (Jurnal EnviScience (Environment Science), 2025)
DAMIU is a business entity that manages drinking water for public consumption needs in bulk form and not in bottled form. Based on the profile of the Surabaya City Health Service for 2019-2021, Tambak Wedi Community Health Center is included in the top 10 in the category of low levels of DAMIU sanitation inspection results for 3 years, namely from 2019-2021. Based on data from the Surabaya City Health Service, in 2019 53.85% did not meet the requirements. In 2020, 44.44% did not meet the requirements. In 2021, 54.44% do not meet the requirements. This research aims to determine the evaluation of the implementation of DAMIU sanitation inspections in the Tambak Wedi Health Center Work Area. This research is descriptive research using quantitative and qualitative research methods. The data obtained was then analyzed and evaluated using a management information system approach by evaluating the input, process, output and outcome variables of management sanitation inspection activities. The research results showed that the input components which included: work plans received a good category, policies received a good category. Human resources include: head of community health center in good category, sanitarian in good category, budget in good category, inspection method in good category, facilities in good category. Process components include: implementation planning obtained a good category, implementation of sanitation inspections obtained a good category, implementation results obtained a good category, employee development in the poor category, raw water processing in a good category, behavior of handlers, cleaning of gallon/outlets in a good category, periodic laboratory examinations in a good category. output component: evaluation of the implementation of inspections in the good category. The outcome component (quality of refillable drinking water) is in the poor category. So there is a need for intensity in training DAMIU employees and increasing the number of health center sanitarian personnel.